Aloe vera in White Leghorn Layer Diet - Moorthy, M.; Mehala, C.; Saravanan, S.; Edwin, S.C. (International Journal of Poultry Science, 2009)
Two hundred and eighty commercial layer chicks belonging to single hatch were purchased from local hatchery, wing banded, weighed and randomly allotted into four treatment groups with four replicates of ten chicks each. The chicks were reared in cages in a gable roofed, open sided house. All the chicks were provided with uniform floor, feeder and waterer space and were reared under standard management conditions throughout the experimental period. Treatment groups were T1- control; T2-0.1% aloe vera powder; T3-0.1% aloe vera + 0.1% Curcuma longa powder and T4-0.1% of aloe vera and 0.1% of probiotic powder There was significant (p